Perspectives of research in graduates of the Public Accounting program of the Francisco de Paula Santander University Ocaña section (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2023)
Research as a training process for public accounting students is a factor that has a positive impact on their professional development and contributes to problem solving for the benefit of organizations. The purpose of this study is to identify the research training needs of the graduates of the public accounting program of the Universidad Francisco de Paula Santander Ocaña, as feedback to improve the training process of the accounting student. Methodologically, it was carried out through a descriptive approach and a field design, through the application of surveys to the graduates of the program, using an intentional sample. The respondents showed weaknesses in their training process, evidencing a gap between the training received in terms of research and the labor market.
Keywords: Professional development; graduates; skills; lines of research; public accounting